Cyberbullying in higher education: A review of the literature based on bibliometric analysis - Muhammad Ashraf, Fauzi (Emerald Group Publishing Limited, 2023)
Purpose: The purpose of this study is to review cyberbullying incidents among students in higher education institutions (HEIs). Cyberbullying has become a threat to students' wellbeing as it penetrates one life due to the pervasive availability of digital technologies. Design/methodology/approach: Through a bibliometric analysis, this study analyzes 361 journal publications from the Web of Science (WoS) based on bibliographic coupling and co-word analysis. Findings: Significant themes were found related to cyberbullying in HEIs, particularly related to the impact and determinants of cyberbullying on students. Bibliographic coupling produces three clusters on the current research fronts, while co-word analysis produces four clusters on the prediction of future trends. Implications of this phenomenon warrant comprehensive intervention by the HEIs management to dampen its impact on students' wellbeing. Findings would enhance the fundamental understanding through science mapping on the prevalent and potential incidence of cyberbullying. Practical implications: Crucial insights will benefit the government, HEIs’ management, educators, scholars, policymakers and parents to overcome this dreadful phenomenon of cyberbullying. Several managerial interventions and mitigation strategies are proposed to reduce and control the occurrence of cyberbullying. Originality/value: This study presents a bibliometric review to uncover the knowledge structure of cyberbullying studies in HEIs.